A non-local frost heave model based on peridynamics theory. (May 2022) - Zhou, Yanqiao; Zhang, Mingyi; Pei, Wansheng; Wang, Yapeng
Abstract: Multitudes of physical phenomena have non-local effects. However, non-local effects are not considered by most soil frost heave models. Peridynamics takes into account non-local interactions, and has not yet been applied in the field of permafrost research. Thus, this study is a preliminary attempt to introduce peridynamics into permafrost research. In this paper, a one-dimensional frost heave model of saturated soils for local theory is established, and then converted to a non-local model of peridynamics. A program of the model is used to verify the model. The comparison between the numerical simulation results and the measured results shows that the model can basically reflect the characteristics of the physical field evolution in the frost heave process of saturated soils. To accelerate the model, the integral term in the mathematical model is deduced into the form of convolution. The modified model can use fast Fourier transform to calculate the convolution term in the model. Compared with the original program, the program accelerated by the fast Fourier transform has a lower memory cost and a higher calculation efficiency.